Steady-state analysis of social responsibility strategy of coal power enterprises from the perspective of game theory - Bang Guo; Yixin Li; Xinping Wang (Heliyon, 2024)
Under the dual-carbon background, coal power enterprises are required to actively fulfill their social responsibility in order to achieve energy saving and emission reduction as soon as possible. Considering the uncertainty of the external environment and the potential conflict of interest of the key stakeholders in the fulfillment of corporate social responsibility, coal power enterprises are not always positive in fulfilling their social responsibility. This paper combines prospect theory and mental account theory with evolutionary game to construct an evolutionary game model involving coal power enterprises, government regulators and the public to study the social responsibility behavior of coal power enterprises. The results of the study show that: (1) The social responsibility behavior of coal power enterprises under the dual-carbon background is a typical cost-driven behavior, and coal power enterprises are more sensitive to costs compared to benefits. (2) The formulation of regulatory policies by government regulators largely depends on the decision inertia of coal power enterprises, and the formulation of regulatory policies by government regulators will also affect the decision inertia of coal power enterprises. (3) The public's strategic choices do not entirely depend on the strategic choices of coal and power enterprises and government regulators, and are more closely related to the setting of the reference point. (4) In addition to the realistic factors, the subjective factors of decision makers are also important factors affecting the fulfillment of social responsibility of coal and power enterprises. Based on the results of the study, this paper proposes countermeasures to enhance the internal driving force of coal power enterprises to fulfill their social responsibility behaviors from the aspects of establishing a communication mechanism, improving the reward and punishment system, and strengthening risk management.